Prediction of Flow Pattern Behaviour Behind Square Cylinder using Computational Fluid Dynamic (CFD) Approach - Nordin, N.; Benard, E.; Kamal, A.H.A; Ahmad, M.T (International Journal of Integrated Engineering, 2020)
The aim of this study is to investigate the flow pattern behaviour by using computational fluid dynamic (CFD) approach. The square profile was chosen in purpose to have a better understanding of the behaviour which is relevant to the engineering applications. Numerical simulation was performed on various turbulence models with the range of Reynolds number from 6000 to 80000 with three incidence angles of 0°, 15°, and 30°. Mesh dependency study was performed with coarse, base and fine meshes. Fine mesh and standard k–ω were chosen as the best meshing and turbulence model to perform the simulation due to the capability in terms of less absolute error on aerodynamic coefficient and clear flow visualisation capture. It was found that the average values of Strouhal number for square profile was 0.12. For this particular study, the changes of incidence angle and variation of Reynolds number gave a significant flow pattern behind a square profile. The size of the vortices became smaller and closer to the structure as the incidence angle increased. At high Reynolds number, it was also observed that the size of the vortices increased progressively. The prediction of flow pattern behind square cylinder was successfully determined by using CFD approach.